2009
DOI: 10.1677/jme-08-0132
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine disruptive chemicals: mechanisms of action and involvement in metabolic disorders

Abstract: Endocrine disruption refers to the ability of chemicals to interfere with hormonal systems, and has raised considerable concern in recent years. Endocrine disruptive chemicals (EDCs) pose a documented risk to wildlife and have the potential to negatively influence human health. This review focuses on the molecular mechanisms of endocrine disruption and the possible involvement of EDCs in metabolic disorders. The first part describes the role of aryl hydrocarbon receptor (AhR) and nuclear receptors (NRs) in med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
161
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(167 citation statements)
references
References 76 publications
2
161
0
4
Order By: Relevance
“…More recently, it has been reported that EDCs are possibly involved in the development of obesity and metabolic syndrome as a number of NRs and AhR are crucially involved in fat metabolism and glucose uptake. 13,72,73) Therefore, exposure to environmental chemicals, including pesticides having NR and AhR activities, not only increases reproductive problems but may also be an exacerbating factor in the development of other debilitating diseases such as metabolic syndrome. Although, to date, 48 members of the NR family have been identified in humans, about half of these are nuclear orphan receptors, the physiological roles and ligands of which are unclear.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, it has been reported that EDCs are possibly involved in the development of obesity and metabolic syndrome as a number of NRs and AhR are crucially involved in fat metabolism and glucose uptake. 13,72,73) Therefore, exposure to environmental chemicals, including pesticides having NR and AhR activities, not only increases reproductive problems but may also be an exacerbating factor in the development of other debilitating diseases such as metabolic syndrome. Although, to date, 48 members of the NR family have been identified in humans, about half of these are nuclear orphan receptors, the physiological roles and ligands of which are unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, in addition to AhR-mediated mechanism, some endocrine disrupting chemical can bind directly to these nuclear receptors either as agonists or as antagonists, thus enhancing or inhibiting the effect of a hormone, respectively. 30,57 Regarding the epidemiological evidence on general populations, a study using the 1999 to 2004 NHANES 28 found a significant 38% increased risk of hypertension among those participants in the highest compared with those in the lowest quartile of serum concentration of total PCBs (odds ratio, 1.38 [95% CI, 1.02-1.87]). Moreover, the congeners identified were not only DL-PCBs (PCB 66 and 118),but also NDLPCBs (PCB 101, 128, and 187).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they are commonly known or suspected to be endocrine active and may interfere at several control points in the hormone signaling pathways in the body. Therefore, the response cascade of natural hormones can either be inhibited or be excessively enhanced, at the wrong time and in the wrong tissue (Swedenborg et al 2009). Endocrine activity of DDT, its structural cognates and lindane can be due to direct binding with hormone receptors, and their conformational similarity with the receptor-binding portions of natural hormones, mainly of the steroid and diphenylether (thyroxine) structural groups (Gregoraszczuk et al 2008).…”
Section: Toxicity As Endocrine Disruptormentioning
confidence: 99%